1930
DOI: 10.1001/archpedi.1930.01940030038004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Suppurative Thyroiditis in Children

Abstract: CHICAGO Acute suppurative thyroiditis in children appears to be extremely uncommon. Accurate statistics as to its frequency are lacking. In the better known monographs on the thyroid gland and in the various treatises on surgery and pediatrics, it is dismissed with a brief statement as to its extreme rarity and grave prognosis. For example, Means and Richardson 1 stated that "in young children acute thyroiditis is ordinarily fatal," while in another paragraph they said that "suppurative thyroiditis may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Acute suppurative thyroiditis is a rare and potentially lifethreatening diagnosis that if unrecognized can lead to complications such as tracheal compression and airway compromise, bacteremia, mediastinitis, or abscess rupture with extension into adjacent structures. [1][2][3][4][5][6] Reviews of AST cases from the early 20th century report mortality rates up to 25%. 2,7 A more recent review of AST cases reported in the literature in the late 20th century reports a much lower, but still significant mortality rate of 3.7% with deaths predominantly occurring in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acute suppurative thyroiditis is a rare and potentially lifethreatening diagnosis that if unrecognized can lead to complications such as tracheal compression and airway compromise, bacteremia, mediastinitis, or abscess rupture with extension into adjacent structures. [1][2][3][4][5][6] Reviews of AST cases from the early 20th century report mortality rates up to 25%. 2,7 A more recent review of AST cases reported in the literature in the late 20th century reports a much lower, but still significant mortality rate of 3.7% with deaths predominantly occurring in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…AST presents as an inflammatory process in the anterior neck. AST is often associated with a recent upper respiratory infection or otitis media, 1 and hematogenous or lymphogenous spread has been suggested as the route of infection 2–4 . It has also been suggested that children and adults are predisposed to thyroid infection by preexisting thyroid disease, direct invasion from contiguous structures, presence of a thyroglossal duct remnant, blunt trauma, or a left pyriform sinus fistula 2–6 .…”
Section: Discussionmentioning
confidence: 99%